School Field Introduction Program as a Strategy to Enhance Biology Education Students’ Teaching Competence : Kegiatan Pengenalan Lapangan Persekolahan (PLP) Sebagai Solusi dalam Mengasah Kemampuan mahasiswa Calon Guru di SMA NW Mataram - Elpana Anisa Sarah; Zuhaeratul Umami (Yayasan Siti Widhatul Faeha, 2025)
The School Field Introduction Program (PLP) is a compulsory activity designed for education students to develop pedagogical, professional, social, and personal competencies. This study aims to describe how the implementation of PLP at SMA NW Mataram serves as an effective solution for honing the abilities of prospective teacher students, particularly in teaching practice, school observation, and classroom management. This article employs a descriptive approach based on direct experiences gained during the PLP I and PLP II programs. The results indicate that PLP provides significant contributions to improving students’ abilities, including lesson planning, content mastery, the use of learning media, and learning evaluation. Thus, PLP functions as a strategic platform. The findings reveal that PLP offers extensive opportunities for students to engage in authentic school environments, allowing them to understand school culture, observe teaching practices, participate in classroom learning, and interact directly with teachers and students. Through guided mentoring from supervising teachers, students develop essential competencies such as lesson planning, mastery of subject matter, classroom communication, classroom management, use of varied learning media, and implementation of learning assessments.o prepare students to enter the professional world as adaptive and competent teachers.